Analysis of THz generation by multicolor laser pulses with various frequency ratios - Zhou, Zhaoyan; lv, Zhihui; Zhang, Dongwen; Zhao, Zengxiu; Lin, C. D. (My University, 2020)
Terahertz (THz) generation in a gas medium is simulated by quantum calculations with multicolor intense laser pulses of various frequency ratios. By correlating THz radiation with the above-threshold-ionization photoelectron spectrum, we confirm that our previously proposed free-free transition model for the generation of THz radiation is also applicable to multicolor pulses. THz photon emissions can proceed through transitions between continuous states with similar energies that have opposite parities. This mechanism predicts that THz waves can be efficiently generated at special two-color laser frequency ratios when the multiphoton mixing condition is satisfied. Applying this model to multicolor fields (sawtooth wave shape), we provide a quantum-mechanical interpretation for the reason for THz radiation enhancement. A scheme combining multiple lasers to raise THz radiation satisfying multiphoton mixing conditions is also proposed.